Penerapan Panduan Nurse-Led Early Mobilization Pada Pasien yang Menjalani Pembedahan Elektif Tulang Belakang - Irman, Irman; Pitaloka, Rika Diah; Rakhman, Isnawan Risqi; Kariasa, I Made; Nova, Prima Agustia; Mulyatsih, MG Enny (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT This study aims to determine the implementation of the Nurse-LED Early Mobilization Guide in patients undergoing elective spinal surgery. This research is an implementation of an Innovation Project which was applied to 10 respondents. Each patient in the study group was mobilized in a sequence starting from right lateral/supine/left, sitting 45o, sitting upright 90o, and dangling sitting mobilization according to the specified time. Post intervention results were evaluated where pain started from the first 24 hours (POD-1) to the third day (POD-3) while functional status after 72 hours post surgery (POD-3). Based on the results, the average Barthel Index in the post-intervention group evaluated on the third day (POD-3) was 15.30 with a standard deviation of 3.40. Meanwhile, the average pain score in the first day post-intervention group (POD-1) was 4.50 with a standard deviation of 0.97. The mean pain score on the second day (POD-2) was 3.60 with a standard deviation of 0.69. Meanwhile, the average pain score on the third day was 2.50 with a standard deviation of 0.70. Conclusion: Nurse-LED early mobilization intervention can be carried out in degenerative disc disease patients undergoing elective spine surgery to improve the patient's clinical outcomes, especially functional status and decreased pain. Keywords: Decreased Pain, Functional Status, Nurse-LED Early Mobilization  ABSTRAK Penelitian ini bertujuan untuk mengetahui Penerapan Panduan Nurse-LED Early Mobilization pada pasien yang Menjalani pembedahan elektif tulang belakang. Penelitian ini merupakan Penerapan Proyek Inovasi yang diterapkan pada 10 responden. Setiap pasien dalam kelompok studi dimobilisasikan dengan urutan mulai dari lateral kanan/supine/kiri, duduk 45o, duduk tegak 90o, dan mobiliasi duduk berjuntai sesuai dengan waktu yang telah ditentukan. Hasil post intervensi dievaluasi dimana nyeri mulai dari 24 jam pertama (POD-1) sampai dengan hari ketiga (POD-3) sedangkan status fungsional setelah 72 jam post operasi (POD-3).  Berdasarkan hasil bahwa rata-rata Barthel Index pada kelompok post intervensi yang dievaluasi pada hari ketiga (POD-3) adalah 15,30 dengan standar deviasi 3,40. Sedangkan rata-rata skor nyeri pada kelompok post intervensi hari pertama (POD-1) adalah 4.50 dengan standar deviasi 0.97. Mean skor nyeri pada hari kedua (POD-2) adalah 3,60 dengan standar deviasi 0,69. Sedangkan rerata skor nyeri pada hari ketiga adalah 2,50 dengan standar deviasi 0,70. Kesimpulan : intervensi Nurse-LED Early mobilization dapat dilakukan pada pasien-pasien degenerative disc disease yang menjalani pembadahan elektif tulang belakang untuk meningkatkan outcome klinis pasien khususnya adalah status fungsional dan penurunan nyeri. Kata Kunci: Penurunan Nyeri, Status Fungsional, Nurse-LED Early Mobilization